MEMBANGUN ETOS KERJA GURU - Syarifuddin Syarifuddin (STIT AL-AMIN KREO TANGERANG, 2018)
In trying to develop teacher work ethos is feeling getting fair treatment: honest, healthy, just and etc. Teachers have to be aware that they are competent people. It means that they have to give big contribution for certain activity till the progress in teaching happens.